Analisis Pengaruh Label Halal pada Kosmetik Terhadap Konsumen Kosmetik di Kecamatan Medan Amplas - Tuti Rahayu; Abdulrahman Sofyan; Arifa Pratami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2020)
This study aims to analyze how much influence the halal label, facial cleanser, and perfume have on cosmetic consumers in Medan Amplas District. The variables used in this research are halal label (X1), facial cleanser (X2), and perfume (X3) for cosmetic consumers (Y). In this study, the method used is a type of research with a quantitative approach. The data source used is primary data. Respondents who were sampled in this study were 43 people. The process of data analysis in this study uses multiple linear regression analysis with the help of SPSS23 to get an overview of the relationship between one variable and another. The results of the study partially show that the halal label variable has a significant effect on cosmetic consumers. The facial cleanser variable partially has a significant effect on cosmetic consumers. While the perfume variable partially does not have a significant effect on cosmetic consumers. The results of the simultaneous regression analysis showed that halal labels, facial cleansers, and perfumes together have a significant impact on cosmetic consumers.